2004
DOI: 10.1002/ajmg.a.30340
|View full text |Cite
|
Sign up to set email alerts
|

Further delineation of Kabuki syndrome in 48 well‐defined new individuals

Abstract: Kabuki syndrome is a multiple congenital anomaly/mental retardation syndrome. This study of Kabuki syndrome had two objectives. The first was to further describe the syndrome features. In order to do so, clinical geneticists were asked to submit cases-providing clinical photographs and completing a phenotype questionnaire for individuals in whom they felt the diagnosis of Kabuki syndrome was secure. All submitted cases were reviewed by four diagnosticians familiar with Kabuki syndrome. The diagnosis was agreed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 44 publications
8
95
0
1
Order By: Relevance
“…5 The cause of KS remains unknown, even though at least 400 patients have been known in a variety of ethnic groups since 1981. [3][4][5][6][7] Some works have ruled out several loci, e.g., 1q32-q41, 8p22-p23.1 and 22q11, from the candidate for KS. [8][9][10][11][12][13] A study of array-based comparative genomic hybridization (CGH) showed a disruption of C20orf133(MACROD2) gene by ~250 kb deletion on a patient with KS 14 , but the following mutation screening for the gene failed to find pathogenic base change within exons in other 19 patients with KS 14 and in 43 Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 The cause of KS remains unknown, even though at least 400 patients have been known in a variety of ethnic groups since 1981. [3][4][5][6][7] Some works have ruled out several loci, e.g., 1q32-q41, 8p22-p23.1 and 22q11, from the candidate for KS. [8][9][10][11][12][13] A study of array-based comparative genomic hybridization (CGH) showed a disruption of C20orf133(MACROD2) gene by ~250 kb deletion on a patient with KS 14 , but the following mutation screening for the gene failed to find pathogenic base change within exons in other 19 patients with KS 14 and in 43 Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Initially believed to have greatest incidence in the Japanese population, 12 KS has since been identified across numerous ethnic groups 2 with equal prevalence in both sexes. 23 It has however, taken a long period of time to determine the molecular basis of the condition owing to the complexity of the condition itself, and recent discoveries are likely to be attributable to the availability of cost effective and efficient sequencing technologies. The numerous inconclusive attempts at determining the causative gene have surely not been in vain, as it is the findings from inconclusive studies that often formed the foundations for successive ones, and may still be relevant in the search for the 'other' implicated genes unaccounted for by MLL2 gene defects.…”
Section: Resultsmentioning
confidence: 99%
“…The findings by Rodriguez et al 21 , were further supported with research by Su et al 22 , as they were also able to identify features of KS in a 13-year-old female with Turner syndrome mosaicism 45,X/46,X,r(X), and incomplete XIST gene expression on her ring X chromosome. Limitations to this theory, however, included the inability to extrapolate these findings to the cause of KS in male patients; with a potential argument reflected in the similar prevalence observed between males and females, 23 thus suggesting a common etiological cause to be most likely. In light of recent findings, however, pre-existing data pertaining to the significance of the X chromosome in this etiology may indeed still be of great relevance.…”
Section: Early Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…festations include early breast development in infant girls (25%), neonatal hypoglycemia (7-8%), persistent hypoglycemia (1%), and diaphragmatic defects (4-8%) [Niikawa et al, 1981;Geneviève et al, 2004;Adam and Hudgins, 2005;Armstrong et al, 2005]. Recently, mutations in the MLL2 gene were identified in KS patients.…”
mentioning
confidence: 99%